Multi-crosslinkable self-healing polysilsesquioxanes for the smart recovery of anti-scratch properties - Jo, Young Yeol; Lee, Albert S.; Baek, Kyung-Youl; Lee, Heon; Hwang, Seung Sang (ELSEVIER SCI LTD, 2017)
A series of multi-crosslinkable, self-healing, ladder-structured polysilsesquioxane inorganic-organic hybrid materials were developed to enhance the mechanical properties through tandem UV-curing and Diels-Alder chemistry. The introduction of UV-curable acryl- or epoxy groups allowed for a higher degree of crosslink density while bringing the inorganic backbones closer together for highly efficient self-healing properties, all with a singular material as the ternary organic functional groups consisting of UV-curable function, diene, and dienophile were tethered to the well-defined inorganic backbone. Exceptional thermal stability (> 400 degrees C), optical transparency (> 95%), solution processability, as well as robust surface mechanical properties in both bulk (pencil hardness 6H) and nanoscale (elastic modulus > 9 GPa), properties which can be adroitly recovered through mild and rapid thermal treatment hold great promise for next generation hybrid smart coating materials for application in optoelectronic devices. (C) 2017 Elsevier Ltd. All rights reserved.
Keywords: UV-CURABLE POLYSILSESQUIOXANE; STRUCTURED POLYSILSESQUIOXANE; POLYMERIC MATERIALS; CARBON NANOTUBES; MEMBRANES; NANOCOMPOSITES; NANOPARTICLES